Effects on cardiorespiratory fitness of moderate-intensity training vs. energy-matched training with increasing intensity - Reuter, Marcel; Rosenberger, Friederike; Barz, Andreas; Venhorst, Andreas; Blanz, Laura; Roecker, Kai; Meyer, Tim (Frontiers in Sports and Active Living, 2024)
Introduction The present study investigated the role of training intensity in the dose–response relationship between endurance training and cardiorespiratory fitness (CRF). The hypothesis was that beginners would benefit from an increase in training intensity after an initial training phase, even if the energy expenditure was not altered. For this purpose, 26 weeks of continuous moderate training (control group, CON) was compared to training with gradually increasing intensity (intervention group, INC) but constant energy expenditure. Methods Thirty-one healthy, untrained subjects (13 men, 18 women; 46 ± 8 years; body mass index 25.4 ± 3.3 kg m−2; maximum oxygen uptake, VO2max 34 ± 4 ml min−1 kg−1) trained for 10 weeks with moderate intensity [3 days/week for 50 min/session at 55% heart rate reserve (HRreserve)] before allocation to one of two groups. A minimization technique was used to ensure homogeneous groups. While group CON continued with moderate intensity for 16 weeks, the INC group trained at 70% HRreserve for 8 weeks and thereafter participated in a 4 × 4 training program (high-intensity interval training, HIIT) for 8 weeks. Constant energy expenditure was ensured by indirect calorimetry and corresponding adjustment of the training volume. Treadmill tests were performed at baseline and after 10, 18, and 26 weeks. Results The INC group showed improved VO2max (3.4 ± 2.7 ml kg−1 min−1) to a significantly greater degree than the CON group (0.4 ± 2.9 ml kg−1 min−1) (P = 0.020). In addition, the INC group exhibited improved Vmax (1.7 ± 0.7 km h−1) to a significantly greater degree than the CON group (1.0 ± 0.5 km h−1) (P = 0.001). The reduction of resting HR was significantly larger in the INC group (7 ± 4 bpm) than in the CON group (2 ± 6 bpm) (P = 0.001). The mean heart rate in the submaximal exercise test was reduced significantly in the CON group (5 ± 6 bpm; P = 0.007) and in the INC group (8 ± 7 bpm; P = 0.001), without a significant interaction between group and time point. Conclusion Increasing intensity leads to greater adaptations in CRF than continuing with moderate intensity, even without increased energy expenditure. After 26 weeks of training in the moderate- and higher-intensity domain, energy-matched HIIT elicited further adaptations in cardiorespiratory fitness. Thus, training intensity plays a crucial role in the dose–response relationship between endurance training and fitness in untrained but healthy individuals. Clinical Trial Registration https://www.drks.de/DRKS00031445, identifier DRKS00031445.